Marketing channel and value chain analysis of Bombay duck and ribbon fish in Coxs Bazar area of Bangladesh - Ahsan, MK; Ghosh, SK; Runa, NS; Hasan, MM; Kamal, M (Progressive Agriculture, 2016)
A study was conducted to investigate marketing channel and value chain of two commercially important marine fish species in Coxs Bazar area, Bangladesh, namely, Bombay duck Harpodon nehereus and Ribbon fish, Trichiurus haumela. Three types of markets were found in the study namely primary, secondary and retail markets. The number of sample fishermen and intermediaries were 120. About 4 to 5 intermediaries were found to be involved in the each marketing chain and this group is believed to make huge profit, thus the prices of fishes were very high in the final consumer market. Marketing margin for fresh Bombay duck and ribbon fish were 29% and 28% and dried Bombay duck and dried ribbon fish were 35% and 19% of consumer purchase price, respectively. Poor transport facilities and huge number of intermediaries in the marketing channels were the main problems of marine fish marketing channel. Government intervention in the marketing channel is necessary for sustainable fish marketing systems. Progressive Agriculture 27 (2): 222-227, 2016